جماليات التكرار في الخطاب الشعري الشعبي بمنطقة سوف بين الميزة الصوتية والقيمة البلاغية (El-Wahat Journal for Research and Studies, 2021)
The repetition is a stylistic phenomenon and it contributes greatly to the formation of the inner rhythm of the poetic text and its stabilization. It is also one of the most important vocal phenomena that characterized the popular poetic discourse in the Suof region. It is considered as one of the essential elements in building the popular poetic text and maintaining its Coherence and harmony in addition to the rhetorical and semantic value, the popular poet often resort to repetition to reach the rhetorical and acoustic value, and then add an aesthetic touch on the poetic text Key words-  Repetition, voice, poetry, popular, eloquence, rhythm.